2017
DOI: 10.3889/oamjms.2017.150
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Cord Blood Immunoglobulin E and Maternal Immunoglobulin E with Birth Order and Maternal History of Allergy in Albanian Mother/Neonate Pairs

Abstract: BACKGROUND:Previous studies reported that familial factors such as birth order and mothers atopy might influence cord blood levels and development of allergies.AIM:The aim of the study was to evaluate the relationship of cord blood IgE and maternal IgE with birth order and mothers history of allergy in Albanian mother/neonate pairs.MATERIAL AND METHODS:Study population represented 291 mother-infant pairs. Mothers were interviewed with a questionnaire for personal history of allergy and pregnancy history wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…In this study, we found that CB-IgE levels were not normally distributed and that most CB-IgE levels were below 0.5 kU/L, as stated in previous reports. 9 A total of 268 (27.10%) infants had elevated CB-IgE (≥0.5 kU/L), which was similar to Ferguson et al 13 (19.30%) and Chieh-An Liu et al's (23.70%) reports. 14 Most studies have shown that elevated CB-IgE levels have a role in the future development of allergic diseases.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this study, we found that CB-IgE levels were not normally distributed and that most CB-IgE levels were below 0.5 kU/L, as stated in previous reports. 9 A total of 268 (27.10%) infants had elevated CB-IgE (≥0.5 kU/L), which was similar to Ferguson et al 13 (19.30%) and Chieh-An Liu et al's (23.70%) reports. 14 Most studies have shown that elevated CB-IgE levels have a role in the future development of allergic diseases.…”
Section: Discussionsupporting
confidence: 79%
“…[4][5][6] Nowadays, although various studies demonstrated that elevated CB-IgE is affected by some different factors including maternal, paternal, placenta, and fetal characteristics, findings on each factor have been inconclusive and discordant. [7][8][9][10] And results remain difficult to compare because of the influence of genetics and different ethnic groups on the CB-IgE. 11,12 Regarding the scarcity of studies about CB-IgE in Chinese Han newborns, more studies are needed to be performed on different populations and situations.…”
Section: Introduction and Objectivesmentioning
confidence: 99%